Evaluation of effectiveness of COVID-19 training of tertiary health care workers - Thakre, Sushama S.; Thakre, Subhash B.; Jadhao, Ashok; Dass, Ruhi; Dhoble, Manjusha A.; Tiwari, Priti N. (International Journal Of Community Medicine And Public Health, 2020)
Background: Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. Most people infected with the COVID-19 virus experience mild to moderate respiratory illness and recover without requiring special treatment. Older people or patients with co-morbidities have been observed to develop a serious illness. Figures from health resources and media reports show high proportion of infection rates and deaths amongst the health care workers (HCW). Thus, a training was conducted to assess the knowledge of the health care workers regarding coronavirus infection and their preparedness to fight against the ongoing pandemic. Methods: A cross sectional study was conducted at Indira Gandhi Government Medical College, Nagpur. This study was carried out from 26th March to 24th April 2020. Total 486 participants (health care workers) who were present at the time of pre-test and post-test during the training were included. Results: In the present study, all the 486 participants filled the pre-test and post -test forms. The mean pre-test and post test scores of all the participants were found to be 17.73 (±5.004 SD) and 20.93 (±5.033 SD) respectively. The difference between the means was observed to be significant. Conclusions: This study reflects that the training was quite effective which is evident from the pre-test and post-test assessment among the health care workers. But there is a need to create higher level of awareness amongst the younger group of doctors as they are the backbone of health care system.